INSTAGRAM DIGITAL MARKETING IN THE PUBLIC SECTOR: A CASE STUDY AT THE VOCATIONAL AND PRODUCTIVITY TRAINING CENTER SIDOARJO - Agustinus Samuel Wijaya; Leonard Adrie Manafe; Abdul Chamid (STMIK Indonesia Banda Aceh, 2026)
Digital transformation has changed the marketing paradigm in the public sector, including vocational training institutions. This study aims to identify the digital marketing strategy of the Sidoarjo Vocational and Productivity Training Center (BPVP) through Instagram, evaluate the effectiveness of various types of content, measure their impact on increasing training program enrollment, and provide strategic recommendations for future optimization. Using a qualitative approach with a single case study design, data were collected through systematic observation of the official Instagram account, in-depth interviews with purposively selected informants, and analysis of institutional documents. These were then analyzed using a qualitative analysis model with triangulation and member checking to ensure validity. The results show that an educational value-based content strategy generates superior organic engagement compared to direct promotion, where short educational video content serves as a catalyst for attention and interest through algorithmic amplification, while alumni testimonials activate a social proof mechanism that reduces uncertainty for potential participants at the desire stage. However, optimal utilization of Instagram is hampered by bureaucratic structural limitations including limited human resources, budget, a multi-tiered content approval process, and difficulties in measuring return on investment. The conclusion confirms that Instagram is an effective digital marketing instrument for increasing public awareness and interest in vocational training programs, but its potential has not been fully realized due to institutional constraints, so optimization requires structural reforms in the form of appointing dedicated digital marketing personnel, streamlining content approval protocols, and integrated tracking infrastructure in addition to tactical optimization of content.